Raman Spectra Analysis for Growth Time Dependence of Single-Walled Carbon Nanotubes from Co Catalyst - Asyadi Azam, Mohd; Mohamed, Mohd Ambri; Shih, HA; Shikoh, Eiji; Fujiwara, Akihiko (2009)
In achieving optimum growth yield of CNTs, appropriate parametric study is still highly required for researchers using alcohol catalytic chemical vapor deposition (ACCVD) method. Here we report our research on growth time dependence analysis of SWCNTs from Co catalyst thin-films. We used Raman spectroscopy as a measurement tool with various laser excitations applied in order to study SWCNTs grown behavior and their structural properties.